Retrospective Analysis of 52 Cases of Enteric Fever in a Tertiary Care Hospital in Dhaka City (Bangladesh Journal of Medicine, 2013)
Enteric fever remains a serious problem in developing countries. School aged children and young adults are mainly the sufferer. Salmonella typhi infection results in a clinical syndrome that varies widely in presentation; especially in new antibiotic era. Records of 52 enteric fever cases who were admitted to BSMMU, from July 2007 to June 2008 was reviewed and information was recorded in a prescribed form. Descriptive analysis was done through SPSS. Mean age was 6.7±4 years and male: female ratio was 1.2: 1. Most common presenting features were fever in 100% cases, abdominal pain 40% cases, vomiting 35% and diarrhea, constipation 10%cases. Hepatomegaly was present in 71% and splenomegaly in 52% cases. In our study32% of children were under 5 years; and the result is similar with some other studies. Typhoid fever is still a disease which is difficult to diagnose. In some cases of delayed response antibiotic may be required for longer duration where patients became afebrile after 10 days or more from starting antibiotic. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13614 Bangladesh J Medicine 2010; 21: 71-73